Exploring the Impact of Domestic Violence on the Quality of Life among Housewives in Multan City - Kiran, Samra; Taelah, Mahin; Ashraf, Samima; Dawood, Samra (Pakistan Journal of Humanities and Social Sciences, 2023)
The purpose of this study was to investigate how domestic violence affects the quality of life of Multan housewives. The sample of the study was selected through the use of the Snowball technique which was comprised of 200 housewives. To classify the population based on the characteristics of qualification, gender, marital status, and age, researchers applied purposive sampling. The age of the participants was between 25-45 years. The target sample consisted of 300 housewives but due to the sensitivity of the issue, the researchers could contact only 244 housewives, and among them, only 200 agreed to participate in this research. To measure family abuse a tool was administered with various subscales (Hussain, 1998). Endicott, Nee, Harrison, and Blumenthal (1993) created the quality of life Enjoyment and Satisfaction questionnaire consisting of 15 items and researchers carried out the analysis of variance, t-test, basic regression analysis, descriptive statistics, and reliability (Cronbach's Alpha). The results revealed that the major thing that affects women’s quality of life is domestic violence. Moreover, this study also revealed that factors such as qualification and social status don’t have any discernible effects on domestic violence. Meanwhile, the age and duration of marriage can affect their domestic violence. Due to the constrained sample and limited respondent turnout, those women should also be included in the study who have not received formal education and are living in other Punjab districts. Moreover, questions could be designed in such a way that can help to assess the reactions of respondents, instead of asking them what they mean by their answers.